Insights into the reliability of Ni/Cu plated p-PERC silicon solar cells. (September 2017) - Dang, Chi; Labie, Riet; Simoen, Eddy; Tous, Loic; Russell, Richard; Duerinckx, Filip; Mertens, Robert; Poortmans, Jef
Abstract: Selective laser ablation of dielectric layers in combination with plated Ni/Cu/Ag contacts have been investigated by many photovoltaic researchers. Despite that there has been quite some practical progress on improved processing, the reliability of plated Ni/Cu/Ag cells still needs further insight and understanding. In this paper, the impact of laser induced defects that result from a ps-laser (wavelength 355nm) ablation on the performance of p-type PERC cells has been studied. A thermal stress experiment at 235 o C is applied. It is shown that the defects formed during the laser ablation process do indeed decrease the cell performance. A higher laser fluence results in lower fill factor and therefore lower efficiency. Moreover, the cells with higher laser fluence ablation degrade faster compared to the cells which had lower laser fluence to open the dielectric layer. The second part of the paper focuses on characterization of the p-n junction of the laser ablated cells by Deep Level Transient Spectroscopy (DLTS) before and after thermal ageing. A hole trap around 80K was found for all samples, which is related to point defects induced during the cell processing. A broad peak around 200K observed for the ablated cells with high laser fluence could correspond to dislocations induced by the laser ablation. This peak is shifted to higher energy (closer to the silicon mid-gap) after annealing, which may be due to impurity decoration during the annealing.